The effectiveness of a body positioning device for controlling patient movement and additional sedative use during endoscopic retrograde cholangiopancreatography: A retrospective analysis - Haruka Masuda; Tsutomu Nishida; Kengo Matsumoto; Dai Nakamatsu; Shiro Hayashi; Masashi Yamamoto (DEN Open)
Abstract Background Endoscopic retrograde cholangiopancreatography requires precise body movement control for procedural safety and efficiency. Sedatives are commonly used but pose risks, especially in elderly patients. This study evaluated the effectiveness of the Medo V‐Fix device in controlling patient movement during endoscopic retrograde cholangiopancreatography. Methods Of 1723 endoscopic retrograde cholangiopancreatography procedures performed between January 2021 and March 2024, 1,528 were analyzed after excluding cases with missing data. Patients were divided into two groups, the device group (n = 697) and the nondevice group (n = 831). The groups were compared with respect to body movement control, additional sedative administration, sedation‐related complications, and procedure discontinuation. Results Baseline characteristics were similar between the groups. Body movement control was better with the device (good, 65.7%; poor, 24.0%; and very poor, 10.3%) than without it (good, 48.1%; poor, 30.7%; and very poor, 21.2%; p < 0.0001). The device reduced the need for manual assistance and additional sedatives. Fewer patients in the device group (9.5% vs. 15.6%, p = 0.0003) required an additional thiopental dose, and the dose was lower (4.5 mg vs. 6 mg, p = 0.0015). No procedure discontinuation occurred in the device group, whereas five discontinuations occurred in the nondevice group. Although hypoxemia was more frequent in the device group (14.5% vs. 8.8%, p = 0.0005), no severe adverse events occurred. Conclusions The Medo V‐Fix device significantly improved body movement control and reduced the need for additional doses of sedatives and manual intervention. Despite a higher incidence of mild hypoxemia, these events were appropriately managed with routine monitoring, indicating that the device increases procedural safety and efficiency.